2002
DOI: 10.1111/1532-7795.00027
|View full text |Cite
|
Sign up to set email alerts
|

Youth Civic Engagement in the Twenty‐First Century

Abstract: We enter the 21st century contending with the end of the Cold War's legacy of political uncertainty, expecting youth to play a significant part in the search for new principles that will bring about stability in the world political order. In forging the future, youth will have to collaborate with adults, but on terms more fitting of the historical circumstances that lie ahead than those of the past. This was the framework adopted by a group of social scientists who held several discussions to reflect on the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
263
0
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(283 citation statements)
references
References 28 publications
5
263
0
15
Order By: Relevance
“…Their social identities relate to the groups they want to be part of and correspondingly how members of that group act (Hogg & Terry, 2000). Adolescence is the prime time for identity formation (Youniss et al, 2002;Youniss, McLellan, & Yates, 1997). It is during adolescence that individuals' self-categorizations related to their political ideologies begin to crystallize (Flanagan, 2009).…”
Section: Political Socialization and Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…Their social identities relate to the groups they want to be part of and correspondingly how members of that group act (Hogg & Terry, 2000). Adolescence is the prime time for identity formation (Youniss et al, 2002;Youniss, McLellan, & Yates, 1997). It is during adolescence that individuals' self-categorizations related to their political ideologies begin to crystallize (Flanagan, 2009).…”
Section: Political Socialization and Youthmentioning
confidence: 99%
“…Combined with parental and community influences, schools can boost students' civic interest and engagement (Youniss et al, 2002), despite reports suggesting today's youth view government and politics with distrust, disengagement, and apathy (Gordon & Taft, 2011). Although youth tend to be disinterested in politics, exigent events, such as wars and scandals, can heighten students' interest in politics and "leave an indelible impression" (Niemi & Hepburn, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it seems to be appropriate to understand political self-efficacy as composed of several particularized efficacy beliefs pertaining to different political domains and levels (Bandura, 1997). We assume that, for adolescents, political self-efficacy for local politics is particularly important because this political level is more accessible to adolescents and closer to their everyday lives than national or global politics (Cammaerts, Bruter, Banaji, Harrison, & Anstead, 2016;Youniss et al, 2002).…”
Section: )mentioning
confidence: 99%
“…Examples abound in which young people played a fundamental role as social activists and change-makers in their countries, communities, schools, neighborhoods and families (Hart, 1992;Youniss et al, 2002). They have affected policy change and influenced broad-based behavioral norms related to a wide range of issues, including education, social health, peacekeeping, and environmental protection (O'Donoghue et al 2002).…”
Section: Collective Actionmentioning
confidence: 99%
“…Past research has shown those who are engaged in this way during adolescence are more likely to continue to actively engage throughout youth and adulthood (Colby & Damon, 1992;Haste, 2003Haste, , 2004Kahn & Westheimer, 2003;Pittman et al, 2007;Watts & Flanagan, 2007;Youniss & Hart, 2005;Youniss et al, 2002;Youniss & Yates, 1997). As people of all age, cultural and socioeconomic groups come to believe they can help shape organizations, communities and society, and actually have opportunities to do so, these institutions will come to more closely reflect the values and meet the needs of all their members (Sirianni and Friedland, 2001;Verba, Schlozman & Brady, 1995;Zeldin et al, 2007).…”
Section: Benefits Of Collective Actionmentioning
confidence: 99%